Key Factors and Trends in Transportation Mode and Carrier Selection - Keith Roberts (Pursuit - The Journal of Undergraduate Research at the University of Tennessee, 2012)
Companies across the country must deal with the daily question of determining the best way to get their product in the hands of their customers. Weighing all of the various factors that play into this decision can prove to be very difficult at times, and these factors are ever changing as the market fluctuates with varying consumer demand which, in turn, affects the demand for transportation. This paper will look into these factors and relevant market trends to determine what factors play the largest role in a company’s decision of how to deliver its products, focusing specifically on the modal and carrier choice decision process. Market trends such as shrinking capacity, tightening cost structures, and the growing importance of environmental friendliness all will be shown to play a significant role in this decision-making process.
Keywords: Transportation